2017
DOI: 10.1093/carcin/bgx051
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic copper and zinc biomarkers and colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort

Abstract: Adequate intake of copper and zinc, two essential micronutrients, are important for antioxidant functions. Their imbalance may have implications for development of diseases like colorectal cancer (CRC), where oxidative stress is thought to be etiologically involved. As evidence from prospective epidemiologic studies is lacking, we conducted a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort to investigate the association between circulating levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 40 publications
4
76
1
Order By: Relevance
“…Biomarkers using TEs attracted more attention following the reporting of evidence from previous studies on TEs and disease risk 41 . TEs have been used for differentiating to patients with and without cancer such as in breast cancer 42 , lung cancer 43 , prostate cancer 44 , and CRC 45 . Although TEs have attracted a lot of attention as potential cancer biomarkers, the cut-off values of the respective TEs have not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers using TEs attracted more attention following the reporting of evidence from previous studies on TEs and disease risk 41 . TEs have been used for differentiating to patients with and without cancer such as in breast cancer 42 , lung cancer 43 , prostate cancer 44 , and CRC 45 . Although TEs have attracted a lot of attention as potential cancer biomarkers, the cut-off values of the respective TEs have not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Data from case–control studies indicate higher copper levels, lower zinc levels, or higher copper/zinc ratio in patients with various cancers, including HCC . Two nested case–control studies within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort have observed that serum zinc levels were inversely and copper/zinc ratio was positively associated with risk of HCC and colorectal cancer, whereas higher serum copper levels were associated with increased risk of colorectal cancer, but not with risk of HCC . However, findings from the Shanghai Women's Health Study (SWHS) and the Shanghai Men's Health Study (SMHS) showed no association between dietary intake of copper and zinc and liver cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Two nested case-control studies within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort have observed that serum zinc levels were inversely and copper/zinc ratio was positively associated with risk of HCC and colorectal cancer, whereas higher serum copper levels were associated with increased risk of colorectal cancer, but not with risk of HCC. 20,21 However, findings from the Shanghai Women's Health Study (SWHS) and the Shanghai Men's Health Study (SMHS) showed no association between dietary intake of copper and zinc and liver cancer risk. 22 With regard to cancer progression, data from a French cohort study and the National Health and Nutrition Examination Survey (NHANES) have linked higher serum levels of copper and lower zinc with increased overall cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, copper overload has been related to several health disorders including Wilson's, Parkinson's, Alzheimer's, and Huntington's diseases . Altered copper levels, and OS, have been associated with cancer progression; while some Cu(II) complexes exhibit anticancer properties . In addition, the role of synthetic copper nucleases on OD‐related processes is an emerging field of investigation .…”
Section: Introductionmentioning
confidence: 99%